2010
DOI: 10.1152/ajpgi.00327.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human epithelial tight junction proteins by Lactobacillus plantarum in vivo and protective effects on the epithelial barrier

Abstract: Karczewski J, Troost FJ, Konings I, Dekker J, Kleerebezem M, Brummer RM, Wells JM. Regulation of human epithelial tight junction proteins by Lactobacillus plantarum in vivo and protective effects on the epithelial barrier. Am J Physiol Gastrointest Liver Physiol 298: G851-G859, 2010. First published March 11, 2010; doi:10.1152/ajpgi.00327.2009.-Lactobacillus plantarum, a commensal bacterium of humans, has been proposed to enhance the intestinal barrier, which is compromised in a number of intestinal disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
409
3
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(439 citation statements)
references
References 50 publications
20
409
3
7
Order By: Relevance
“…Tight junctions are the major determinants of paracellular permeability. Although changes in epithelial tight junction protein expression have been studied extensively in monolayers stimulated by cytokines, challenged by bacteria, or exposed to aspirin (16)(17)(18)(19)(20)(21)(22), much remains to be understood about barrier disruptive changes under inflammatory conditions in vivo. Our results have indicated that the probiotic mixture VSL#3 protects colonic epithelial barrier function in acute DSS colitis, as demonstrated by effective prevention of increased Evans blue dye uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Tight junctions are the major determinants of paracellular permeability. Although changes in epithelial tight junction protein expression have been studied extensively in monolayers stimulated by cytokines, challenged by bacteria, or exposed to aspirin (16)(17)(18)(19)(20)(21)(22), much remains to be understood about barrier disruptive changes under inflammatory conditions in vivo. Our results have indicated that the probiotic mixture VSL#3 protects colonic epithelial barrier function in acute DSS colitis, as demonstrated by effective prevention of increased Evans blue dye uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics have been shown to favorably influence the development and stability of the microbiota, inhibit the colonization by pathogens, influence the mucosal barrier by trophic effects on the intestinal epithelium, protect against physiological stress, and stimulate both specific and nonspecific components of the immune system. 139,[157][158][159][160][161][162][163] Probiotics may well replace antibiotics whose resistance has been steadily increasing. Similar to the effects of microbiota, the effects of administration of probiotics and prebiotics are being intensively studied.…”
Section: Probiotics and Prebiotics In Disease Prevention And Therapymentioning
confidence: 99%
“…Lactobacillus plantarum has been proposed as probiotic, and several studies have been performed that show its capacity to resist transit through the gastric tract, ability to colonise the host gut, safety and potential health benefits such as cholesterol reduction (de Vries et al 2006;Georgieva et al 2009;Karczewski et al 2010).…”
Section: Introductionmentioning
confidence: 99%